Clinical Legal Education for Human Rights Issues: How Students Can Implement Their Basic Knowledge of Human Rights in Reality - Ridwan Arifin (The Indonesian Journal of International Clinical Legal Education, 2019)
Human rights was recognized as a fundamental issue both international community and regional community like ASEAN. The student capability to transfer their knowledge concerning to the human rights was become very important thing for legal development as well as law enforcement. Through clinical legal education, students were be prepared to be available bring a justice in their real lives. Clinical legal education which specifically for human rights issues prepares student for lifelong careers in social justice advocacy around the globe. Through the Clinic, students join a community advocates working to promote human rights and recalibrate the global power imbalances that drive economic and political inequity, exploitation, threats to physical security, poverty, and environmental injustice. Through fact-finding, reporting, litigation, media engagement, advocacy, training, and innovative method, the Clinic seeks to prevent abuse, advance respect for human rights, and promote accountability for violations. The paper divided into three main folds, first, how was the human rights issues on clinical legal education in some practices, second, how was the student encourage the basic knowledge of human rights through clinical legal education, and three, how was the student use their knowledge in their reality lives. The paper emphasized that, at the intersection of theory and practice, the Clinic can be used as a laboratory for testing and modeling new and innovative modes of human rights work, and seeks to be a model of rigorous and critical human rights advocacy. This includes a focus on enhancing human rights methods through interdisciplinary partnerships, critical reflection on human rights practice, and sustainable advocacy through attention to vicarious trauma and resilience.